Optimization of Trypsin-like Protease Production by Lactobacillus plantarum FNCC 0270 using Response Surface Methodology - Trismilah,; Nurhasanah, Astutiati; Sumaryono, Wahono; Malik, Amarila; Sadikin, Mohamad (UI Scholars Hub, 2015)
The purpose of this study was to get optimum medium composition and agitation to trypsin-like protease production by Lactobacillus plantarum FNCC 0270. The medium composition and agitation for enzyme production was optimized using Central Composite Design and Response Surface Method with Design Expert software version 7.1.5 Fermentation was carried out in erlenmeyer flasks at initial pH 8, 37 °C, using an incubator shaker at 87.5 rpm. The best results showed an enzyme activity of 1.0 mU/mL, a protein level of 0.557 mg/mL, and desirability value of 0.740. Numerical optimization was performed to approach the ideal state of the fermentation or the desirability value of 1. The medium composition containing of 3.64% baker's yeast, 1.21% glucose, and 0.13% skim milk was used for the fermentation. The enzyme activity of 1.51 mU/mL and protein level of 0.205 mg/mL can be achieved. After numerical optimization, the fermentation process was verified in erlenmeyer flasks with incubator shaking at 77 rpm, initial pH 8, 37 °C, and 15 h fermentation. The verification results showed that the enzyme activity of 1.273 ± 0.227 mU/mL and protein level of 0.248 ± 0.012 mg/mL.